An Interactive Educational Platform for LEO Satellite Mission Design: A Case Study of a Web-Based Orbit Design Application - Sigit, Robby Kevin Putra; Setiawan, Dhoni Putra; Edwar, Edwar (eProceedings of Engineering, 2025)
This study presents the development of a web-based application designed as an interactive educational platform for Low Earth Orbit (LEO) satellite mission design. The platform addresses the gap left by costly and complex professional software, making the fundamental principles of orbital mechanics, constellation design, and communication link analysis more accessible to students and enthusiasts. The application provides an integrated platform for designing, simulating, and analyzing satellite missions. The system is built with an interactive user interface that offers both 2D and 3D visualizations to facilitate an intuitive understanding of complex orbital dynamics. To ensure its validity and reliability, the application underwent a series of rigorous tests. The results were validated by comparing the application's outputs with theoretical calculations derived from fundamental principles of orbital mechanics, as well as results from a high-fidelity numerical propagator like NASA’s General Mission Analysis Tool (GMAT). Key findings showed very high accuracy, including negligible differences in orbit propagation compared to manual calculations, precise constellation placement, and a minimal discrepancy of 0.05 km in coverage radius. Furthermore, the prediction of ground station access schedules was proven to be highly accurate, with differences of only a few seconds. Thus, the application serves as a valid, reliable, and user-friendly tool for preliminary LEO satellite mission design, successfully fulfilling its objective of making satellite orbit design more accessible for educational and initial technical assessment purposes. Keywords — LEO, satellite orbit design, constellation, orbit simulation, link budget, web application.